Runway taxi optimisation : case study of Changi Airport - Teo, Darren Jin Song (Nanyang Technological University, 2021)
Air travel has been at a standstill and air passenger traffic at a nadir, due to global lockdowns ever since the onset of the COVID-19 pandemic. While vaccines are being administered across the globe and the world awaits the total eradication of the virus, perhaps it is an opportunity for the airline industry to re-examine its processes and practices to address growing concerns over the environmental issues of air travel. One area which can be taken a look at is the ground movement of aircraft. Taxiing aircraft is a significant contributor to two significant metrics of environmental sustainability in the airline industry – fuel consumption and pollutant emissions. This paper presents a simple approach to quickly optimise the aircraft’s speed profile for a given taxiway route for the objectives of minimising both fuel consumption and pollutant emissions. The approach consists of setting up objective functions and then plotting the relation between the aircraft speed profile and the relevant objective. Results show that the speed profile for minimising fuel burn and pollutant emissions is not necessarily at the point where taxi time is minimised and provides a steppingstone for future – and more comprehensive – work.